Outcomes of Oseltamivir Treatment for H1N1 Infection During Pregnancy: A Retrospective Study - Akdemir, Nermin; Özdemir, Osman; Koç, Filiz (Gynecology Obstetrics & Reproductive Medicine, 2011)
OBJECTIVES: Oseltamivir is an antiviral agent which can be used for treatment and chemoprophylaxis against H1N1 influenza for people at high risk of complications, including pregnant women. In this study, we aimed to present our single center experience about the usage of oseltamivir for H1N1 infection during pregnancy on maternal and fetal outcomes. STUDY DESIGN:Between September 2009 and June 2010, total ten patients who were treated by the diagnosis of swine flue included the study. Oseltamivir was started in all patients as 75 mg twice daily for five days. Because of adverse effects and complications due to H1N1 and oseltamivir, all patients were hospitalized for 5-7 days. All the data concerning about maternal and newborns were analyzed retrospectively. Post partum echocardiography was performed in all newborns and patients. RESULTS: Data of ten patients were analyzed retrospectively. There was not any maternal or fetal death due to H1N1 and oceltamivir theraphy. There was not any premature membrane rupture. Peripartum cardiomyopathy was detected and treated successfully in one patient in whose the disease has not been attributed to H1N1. Combined atrial septal and ventricular septal defect were detected in one newborn and Patent Foramen Ovale was detected in 2 newborns as fetal outcome. CONCLUSION: In this retrospective, study, we found that, H1N1 infection during pregnancy has a good prognosis and without complication for maternal health. Although oseltamivir therapy is safe in pregnant women, it can be associated with cardiac structural cardiac malformations in H1N1 infected pregnancy newborns